Innovation as a way of increasing the competitiveness of the economy - Stojković Hadži Strahinja; Kastratović Edita; Stanković Ljiljana (Trendovi u Poslovanju)
Innovation emerged as a subject of major research in the second half of the twentieth century, so that researchers observe this period as the beginning of the development of innovation studies. The paper presents an analysis of relevant literature that indicates innovation as a significant factor in increasing the competitiveness of the economy. The European System of Innovation Indicators (EIS and IUS) is explained, which enables a comparable assessment of the success of innovation in EU countries, pointing out the relative strengths and weaknesses of their research and innovation systems. In this way, it helps Member States to assess areas that would be good to focus on in order to strengthen their profits in the field of innovation. The paper presents an analysis and a comparative innovation index of Slovenia, Croatia, and Serbia for 2021 according to the IUS methodology.